Individual and community influences on adherence to directives in the event of a plague attack : survey results - Wray, Ricardo J. (2014)
Objectives: During a public health emergency, public health officials issue directives with actions people need to take to protect themselves. Past research has shown that adherence to these directives depends on individual beliefs and circumstances. This report presents new research about the effects of community factors on adherence. Methods: A random digit-dial survey of 936 residents in the St Louis, Missouri, area was conducted in 2008 to assess barriers to and facilitators of adherence to directives issued in response to a hypothetical scenario involving the intentional release of the bacterium that causes plague. Community factors were assessed using characteristics of census tracts for individual respondents. Multilevel modeling was used to understand how individual and community factors contributed to the likelihood of adherence. Results: The majority of participants indicated that they would adhere to 3 distinct directives. Community poverty and ethnic homogeneity as well as individual-level barriers were negatively associated with adherence to a 6-day quarantine. Having children younger than 18 years and being away from home when the directive was called were negatively associated with adherence to a 10-hour quarantine. Logistical concerns were negatively associated with visiting a point of dispensing for prophylactic antibiotics. Conclusions: Our findings establish an empirical basis for the influence of community factors on adherence to public health directives. The influence of community and individual factors on adherence varies across directives. Consequently, communication strategies to disseminate directives and organizational strategies to support them must vary according to the nature of the directives.